2021
DOI: 10.25115/ejrep.v19i53.3444
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Engagement Mediates Self-Efficacy and Classroom Management: Focus on Indonesian Primary Schools

Abstract: Introduction.  The numbers of students with special needs studying in regular classes is increasing every year. This increase has consequences for teachers, who must manage classrooms to meet the students’ diverse needs and characteristics. The contributing factor to successful inclusive education is teachers’ self-efficacy in practicing it. Successful implementation of inclusive education, on the other hand, classroom management can be viewed as performance influenced by the extent to which teachers are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The investigation of the relationship between teacher efficacy and knowledge about EBDs demonstrated a significant correlation between these constructs. Previous studies supported this relationship and reported that teachers with high levels of knowledge display high levels of efficacy, particularly in their teaching abilities (Goddard et al, 2004;Goker, 2021;Gümüş & Bellibaş, 2021;Guskey & Passaro, 1994;Kartal & Dilek, 2021;Latouche & Gascoigne, 2019;Li & Cheung, 2021;Lu et al, 2020;Oliver & Reschley, 2010;Rahmadani & Kurniawati, 2021;Sharma et al, 2012). Although previous studies addressed the relationship between these two constructs, the relationship between knowledge and efficacy was not investigated, specifically concerning working with students with EBDs.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the relationship between teacher efficacy and knowledge about EBDs demonstrated a significant correlation between these constructs. Previous studies supported this relationship and reported that teachers with high levels of knowledge display high levels of efficacy, particularly in their teaching abilities (Goddard et al, 2004;Goker, 2021;Gümüş & Bellibaş, 2021;Guskey & Passaro, 1994;Kartal & Dilek, 2021;Latouche & Gascoigne, 2019;Li & Cheung, 2021;Lu et al, 2020;Oliver & Reschley, 2010;Rahmadani & Kurniawati, 2021;Sharma et al, 2012). Although previous studies addressed the relationship between these two constructs, the relationship between knowledge and efficacy was not investigated, specifically concerning working with students with EBDs.…”
Section: Discussionmentioning
confidence: 99%
“…Classroom management also contributes to teachers' self-efficacy, as shown in 5 studies (Rahmadani & Kurniawati, 2021;Odanga et al, 2022;Jaafar, 2019;Yahaya et al, 2017;Akman, 2021) as well as 4 studies based on the school's psychosocial environment (Amatan & Han, 2019;Zaki & Izwan 2022;Wilson et al, 2018;Reaves & Cozzens, 2018). Meanwhile, 3 studies look into leadership style (Hamzah & Ishak, 2022;Akman, 2021;Taul et al, 2021) and social support (Ramayah et al, 2022;Bakar & Amat, 2022;Hamzah & Ishak, 2021).…”
Section: Research Findings A)mentioning
confidence: 99%
“…The social components, encompassing relationships and empathy with both students and colleagues, are categorized as social in terms of students and colleagues, respectively (Klassen et al, 2013). Furthermore, certain scholars explore the intricacies of understanding teacher work engagement (Granziera, 2019;Rahmadani & Kurniawati, 2021;Wilcox & Lawson, 2018;Zhao et al, 2019). The researchers delved into the nuanced dimensions and theoretical underpinnings of teacher work engagement, providing valuable insights to further illuminate the concept of teacher work engagement.…”
Section: " (P3)mentioning
confidence: 99%
“…The researchers delved into the nuanced dimensions and theoretical underpinnings of teacher work engagement, providing valuable insights to further illuminate the concept of teacher work engagement. For instance, Rahmadani and Kurniawati (2021) conceptualize teacher work engagement in accordance with Klassen et al's (2013) multidimensional view of teacher engagement. This conceptualization posits that engaged teachers showcase involvement in physical, emotional, and cognitive dimensions in their teaching, which, in turn, stimulates students to enhance their dedication to their work.…”
Section: " (P3)mentioning
confidence: 99%
See 1 more Smart Citation